Penyuluhan Dan Pendampingan Masyarakat Tentang Produksi Jamur Tiram Di Desa Jambesari Kecamatan Jambesari Ds Kabupaten Bondowoso - Qoidul Khoir (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
Oyster Mushroom (Pleurotus ostreatus) is one of the commercially edible mushrooms, has high economic value and is prospective as a source of income for farmers. Along with the increasing demand for oyster mushrooms, business opportunities for oyster mushrooms have promising prospects. Based on this, it is necessary to provide counseling and assistance for the production of Oyster Mushroom cultivation in Jambesari Village. The purpose of this service program is through education and demonstrations on how to manufacture and process mushroom growing media (baglog), sterilize mushroom growing media inoculate mushroom seeds into baglog, maintenance, harvesting and packaging in order to build an oyster mushroom cultivation business to improve the community's economy and make it as a superior product. The results of community service in counseling and assisting in oyster mushroom production are: 1). Partners are able to make oyster mushroom growing media by utilizing organic waste which is abundant, cheap and easy to obtain from the surrounding environment, namely sawdust so that sengon wood waste can be utilized so that it can make the environment cleaner and free of waste. 2). Cadres/target groups have expertise in oyster mushroom cultivation. 3). Increasing public knowledge that oyster mushroom products can be used to add nutrition or menus can also increase family income.